Vertical discourse in the communication between non-governmental organization, local government and women’s community-based organizations: analysis from the communication perspective - Pérez Barrenechea, Eliana (2014)
This study explains the vertical discourse observed in the relationship established between a nongovernmental organization for development (NGO), a local government (LG)and community-based organizations (CBO) for food support constituted by rural women in order to “create” citizenship. The analysis is covered from the dialectic perspective taking into account that the vertical nature of such relations is the result of historical exclusion situations and the unequal concentration of power. Common in some Latin American countries,the social-political context of dependent capitalism is considered a reference framework. The study intends to highlight the fundamental role of communication – conceivedas a space of encounter and liberation – for social change. It is evidenced that the lack of communication generates unsustainable vertical relations, promoting changes that are not originated from the individual’s consciousness and practice and extend the reproduction of the existing unequal system.